Analysis of academic desertion among ungraduated mathematics students - Miguel Armando Rodríguez-Márquez; Dagoberto Salgado-Horta; Cristina Pedrosa-Jesús (Institute of Advanced Engineering and Science, 2024)
University dropout is a phenomenon that has played an important role in the undergraduate program in mathematics at the University of Tolima (Colombia), because it has been a program that has high dropout rates semester by semester. To generate the results presented here, the population who was considered was students enrolled in the 2012A-2018B academic period. In this time frame, the information on the factors required to characterize student dynamics is consolidated and evaluated using the Kaplan-Meier statistical model, evaluation of associations, correlations and comparisons using non-parametric statistics. The aim is to determine the individual, academic, institutional, social and economic factors that cause students to drop out. As a result of the analysis in context, the factors that influence the problems of the phenomenon of dropout in this cohort were determined and characterized. This methodology presents causal factors for student retention on which actions should be taken to propose strategies associated with obtaining better percentages of retention and graduation within the Bachelor’s Degree program in Mathematics.